Uruguay : Selected Issues Paper. (IMF Staff Country Reports; Country Report ;, 2011)
This paper estimates cyclically adjusted balances for Uruguay, and discusses methodological and practical implementation issues. In line with standard practice, this paper assumes aggregate fiscal revenue elasticity equal to one. The study also focuses on the cyclically adjusted primary balance, so interest payments are excluded from the analysis. It also estimates Cyclically Adjusted Balances (CABs) for both the consolidated public sector and the general government. The economic development and the credibility of the inflation target are discussed. This study identifies the drivers of the low profitability of Uruguayan banks.